1996
DOI: 10.1055/s-0038-1650575
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Protein C Deficiency in Japanese Subjects Using a Rapid and Nonradioactive Method for Single-Strand Conformational Polymorphism Analysis and a Model Building

Abstract: SummaryWe studied the molecular basis of protein C deficiency in 28 Japanese families including 4 asymptomatic families. Two showed a decreased level of function with a normal antigen concentration consistent with type II protein C deficiency and the remaining 26 showed type I deficiency with decreases in both function and antigen level. All the exons and intron/exon junctions of the protein C gene were studied using a strategy combining polymerase chain reaction (PCR) amplification and rapid nonradioactive si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…However, the PC level of the neonate was only 15% compared to the adults, the first observed onset of thrombosis of the proband with CHPD was at 30 years old, and no symptoms of thromboembotic events at birth had been observed. This condition indicated that the compound heterozygous mutations caused mild PC deficiency, inconsistent with most previous reports of CHPD (Manabe and Matsuda, 1985;Deguchi et al, 1992;Miyata et al, 1996).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…However, the PC level of the neonate was only 15% compared to the adults, the first observed onset of thrombosis of the proband with CHPD was at 30 years old, and no symptoms of thromboembotic events at birth had been observed. This condition indicated that the compound heterozygous mutations caused mild PC deficiency, inconsistent with most previous reports of CHPD (Manabe and Matsuda, 1985;Deguchi et al, 1992;Miyata et al, 1996).…”
Section: Discussioncontrasting
confidence: 81%
“…At present, the database of PROC mutations (www.hgmd.cf.ac.uk/ac/gene.php?gene=PROC) has registered 310 mutations or polymorphisms. F139V has been found in the PC deficiency pedigrees of Chinese and Japanese (Miyata et al, 1996;Zhou et al, 2007). D255H has also been reported in patients with PC deficiency and venous thrombosis (Tsay and Shen, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…[11][12][13][14][15] On the basis of analyses of synthesis rates, posttranslational modifications, and secretion of wild-type PC and mutant PC with single amino acid substitution, we demonstrated that conformational defects resulted in the impaired sorting of abnormal molecules to secretory vesicles in the trans-Golgi network. This impairment may be at least partly responsible for PC deficiency caused by single amino acid substitution.…”
Section: Discussionmentioning
confidence: 99%
“…In the human PC, Asp71 is modified to a ␤-hydroxylated residue and is thought to be involved in high-affinity calcium ion binding. 10 Many clinical reports have shown that patients with decreased circulating levels of PC develop thrombophilia, [11][12][13][14][15] with venous thrombosis in heterozygotes and purpura fulminans in homozygotes. A wide variety of genetic mutations can lead to PC deficiency and PC molecular abnormality.…”
mentioning
confidence: 99%
See 1 more Smart Citation